Analisis Penerimaan Platform ruang GTK Menggunakan Technology Accaptance Model (TAM) Pada guru dan Tenaga Kependidikan di Kota Padang - Embun Suri, Rindang; Rayendra; Hidayanti, Abna; Felicita Amsal, Mutiara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the acceptance of the Ruang Guru dan Tenaga Kependidikan (Ruang GTK) platform using the Technology Acceptance Model (TAM) framework among civil servant (ASN) teachers and education personnel in Padang City. The variables examined include Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Using (ATU), Behavioral Intention to Use (BI), and Actual System Use (AU). A quantitative explanatory approach was employed, with data analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) through SmartPLS version 4.1.1.8. The sample comprised 220 respondents selected via purposive sampling. Results indicate that all five hypotheses were statistically significant: (1) PEOU positively influenced PU (β = 0.775; p = 0.000); (2) PU positively influenced ATU (β = 0.786; p = 0.000); (3) ATU positively influenced BI (β = 0.592; p = 0.000); (4) BI positively influenced AU (β = 0.709; p = 0.000); and (5) PEOU positively influenced BI (β = 0.258; p = 0.000). Model fit evaluation showed SRMR = 0.082 and GoF = 0.662 (strong category). Overall, 90% of respondents accepted the Ruang GTK platform. These findings imply that perceived ease of use and usefulness are key factors driving the acceptance and actual use of government-mandated digital education platforms.